Interwar East Central Europe, 1918-1941 : the failure of democracy-building, the fate of minorities - Ramet, Sabrina P. 1949- HerausgeberIn (Routledge studies in modern European history, 2020)
"This monograph focuses on the challenges which interwar regimes faced and how they coped with them in the aftermath of World War I, focusing especially on the failure to establish and stabilize democratic regimes, as well as on the fate of ethnic and religious minorities. Topics explored include the political systems and how they changed during the two decades under review, land reform, Church-state relations, and culture. Countries studied include Poland, Czechoslovakia, Hungary, Yugoslavia, Romania, Bulgaria, and Albania"--